American Recovery and Reinvestment Act-comparative effectiveness research infrastructure investments: emerging data resources, tools and publications. (November 2014) - Segal, Courtney; Holve, Erin
The Recovery Act provided a substantial, one-time investment in data infrastructure for comparative effectiveness research (CER). A review of the publications, data, and tools developed as a result of this support has informed understanding of the level of effort undertaken by these projects. Structured search queries, as well as outreach efforts, were conducted to identify and review resources from American Recovery and Reinvestment Act of 2009 CER projects building electronic clinical data infrastructure. The findings from this study provide a spectrum of productivity across a range of topics and settings. A total of 451 manuscripts published in 192 journals, and 141 data resources and tools were identified and address gaps in evidence on priority populations, conditions, and the infrastructure needed to support CER.